Appealing Because He Is Appalling Black Masculinities, Colonialism, and Erotic Racism - Kitossa, Tamari (University of Alberta Press, 2021)
This collection invites us to think about how African-descended men are seen as both appealing and appalling, and exposed to eroticized hatred and violence and how some resist, accommodate, and capitalize on their eroticization. Drawing on James Baldwin and Frantz Fanon, the contributors examine the contradictions, paradoxes, and politico-psychosexual implications of Black men as objects of sexual desire, fear, and loathing. Kitossa and the contributing authors use Baldwin's and Fanon's cultural and psychoanalytic interpretations of Black masculinities to demonstrate their neglected contributions to thinking about and beyond colonialist and Western gender and masculinity studies. This innovative and sophisticated work will be of interest to scholars and students of cultural and media studies, gender and masculinities studies, sociology, political science, history, and critical race and racialization. Contributors: Katerina Deliovsky, Delroy Hall, Dennis O. Howard, Elishma Khokhar, Tamari Kitossa, Kemar McIntosh, Leroy F. Moore Jr., Watufani M. Poe, Satwinder Rehal, John G. Russell, Mohan Siddi.